EETSR: Energy Efficient Threshold Sensitive Hierarchical Routing Protocol for Wireless Sensor Network (International Journal of Engineering and Computer Science, 2015)
Wireless sensor Networks (WSNs) has enabled the designers to create autonomous sensors, which can be deployed randomly, without human supervision, for the purpose of sensing and communicating valuable data due to increased use of Wireless sensor Networks (WSNs) in variety of applications. In Wireless Sensor Networks, efficient energy management has a great importance. In this paper, we propose a novel hierarchical routing protocol; Energy Efficient Threshold Sensitive Routing Protocol (EETSR) to prolong network lifetime and stability period. We utilize static clustering with threshold aware transmissions to achieve these targets. Our hybrid protocol is suitable for both proactive and reactive networks. Simulations are done in MATLAB and the results show that our protocol has improved stability period than LEACH, SEP, TEEN. We also implemented the Uniform Random Model (URM) to find Packet Drop to make our scheme more practical.